STRATEGI KOMUNIKASI SOCIAL MEDIA BUZZER @infodenpasar PADA INSTAGRAM DALAM MENYEBARKAN INFORMASI DAN MEMBANGUN OPINI MASYARAKAT KOTA DENPASAR - Ulio; I Putu Adi Saskara; I Wayan Yudhasatya Dharma (UHN IGB Sugriwa Denpasar, 2021)
This research is a qualitative research that examines the SocialMedia Buzzer @Infodenpasar Communication Strategy on Instagram indisseminating information and building public opinion in Denpasar City.This research is very important because in today's digitalization era, theuse of information technology is to facilitate the public in all lines of activityand the flow of information dissemination and exchange is very fast whichoften causes uproar in cyberspace because of the rampant circulation ofhoax or fake news, an account is present. @infodenpasar on Instagram asa social media buzzer with 885 thousand followers / followers to becomecredible and trusted news and information presenter accounts in spreadingnews and information about Denpasar City. In this study, the focus will beon analyzing three problems, namely: (1) Why do the people of DenpasarCity choose social media buzzer @infodenpasar account on Instagram inlooking for news and information about the city of Denpasar ?, (2) How isthe social media buzzer @infodenpasar communication strategy onInstagram in disseminating information and building public opinion inDenpasar City, (3) What are the implications of social media buzzer@infodenpasar on Instagram in spreading information and building publicopinion in Denpasar City?The research method used is a qualitative research method, toachieve the research objectives, relevant and adequate data are required.Researchers as a key instrument, the technique of determining informantsusing a purposive sampling model, while the data collection techniquesused observation, interviews and library studies. The findings of the study include: Reasons for social media users inchoosing the @infodenpasar account as a media in searching for news andinformation about the city of Denpasar, consumer behavior throughseveral stages of the decision making process, namely information search,alternative evaluation, and purchase decisions The communicationstrategy used by @infodenpasar is by using redundancy techniques,canalizing techniques, informative techniques, and persuasive techniques.Furthermore, the implications for the communication strategy of the SocialMedia Buzzer @infodenpasar in disseminating information and buildingpublic opinion in the city of Denpasar include: Implications for CommunityEconomic Development, Implications for Easing Access to Education,Implications for Forming Ethics and Decency, and Implications for Safetyand Smooth Traffic